2022
DOI: 10.1017/wsc.2022.9
|View full text |Cite
|
Sign up to set email alerts
|

A nonnative Palmer amaranth (Amaranthus palmeri) population in the Republic of South Africa is resistant to herbicides with different sites of action

Abstract: Palmer amaranth (Amaranthus palmeri S. Watson) is not native to Africa. Based on the presence and persistence of A. palmeri populations, its invasive status in southern Africa is classified as “naturalized”. Globally, A. palmeri is one of the most troublesome weed species in several crops including soybean [Glycine max (L.) Merr.], maize (Zea mays L.), and cotton (Gossypium hirsutum L.). Certain populations of A. palmeri in various countries were reported to be resistant to herbicides with different sites-of-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 95 publications
0
12
0
Order By: Relevance
“…DNA extraction was performed using the same procedures as described in Matzrafi et al (2017). Primers that were used to sequence the ALS gene and the PCR procedure are described in Reinhardt et al (2022). Sequence analyses and alignment were performed using the BioEdit software (Hall, 1999).…”
Section: Sequencing Of the Als Genementioning
confidence: 99%
See 1 more Smart Citation
“…DNA extraction was performed using the same procedures as described in Matzrafi et al (2017). Primers that were used to sequence the ALS gene and the PCR procedure are described in Reinhardt et al (2022). Sequence analyses and alignment were performed using the BioEdit software (Hall, 1999).…”
Section: Sequencing Of the Als Genementioning
confidence: 99%
“…The nucleotide sequence of the ALS gene was amplified using two pairs of primers (Reinhardt et al, 2022). Sequences were then aligned with each other and compared to the A. thaliana ALS gene, in order to identify the nucleotide substitutions leading to point mutations.…”
Section: Mechanism Of Resistance To Als Inhibitorsmentioning
confidence: 99%
“…Previous research reported that newly introduced A. palmeri populations in the United States, Brazil, Turkey, and South Africa were confirmed to be MHR (Faleco et al 2022;Küpper et al 2017;Mennan et al 2021;Reinhardt et al 2022). Wisconsin researchers reported a recently discovered A. palmeri population was threeway MHR and survived labeled rates of imazethapyr, glyphosate, and atrazine (Faleco et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…10 Seasonal and long-term control of Palmer amaranth is difficult because it has a season-long emergence pattern, vigorous seedling growth, the ability to rapidly replenish the soil seed bank, and a tendency to evolve resistance to herbicides. 9,11,12 From its native origins in the Sonoran Desert, Palmer amaranth populations have spread throughout different areas of the United States, 13 parts of South America, 6 and recently in South Africa, 14 including multiple-herbicide-resistant (MHR) populations, 14 either due to trade of contaminated farm equipment, crop seeds, or other raw food materials. To date, Palmer amaranth has evolved resistance to nine herbicide sitesof-action, including the 4-hydroxyphenylpyruvate dioxygenase (HPPD)-inhibiting herbicides, and numerous MHR Palmer amaranth populations have contributed to its success as an invasive weed.…”
Section: Introductionmentioning
confidence: 99%